Combined UV and Formic Acid Treatment Suppresses Aspergillus flavus and Aflatoxin B1 on Dried Red Chili Powder - Xiaoman Chen; Gang Yang; Yi Zhang; Yaoyao Su; Jun Huang; Aijun Li; Kewei Chen; Muying Du; Zsolt Zalán; Sameh Awad; Jianquan Kan (Foods)
Aflatoxin contamination poses a significant food safety risk, particularly during the storage of dried chili peppers. This study evaluated the efficacy of formic acid treatment, ultraviolet (UV) treatment, and combined UV-formic acid treatment in both preventing and controlling Aspergillus flavus in dried red chili powder. Efficacy was assessed by measuring the growth diameter of A. flavus colonies on un-colonized and already colonized dried red chili powder. The optimal treatment conditions for the UV-formic acid combination were determined through single-factor experiments, orthogonal experiments, and quality assessment. Finally, the effects of the UV-formic acid combination on the cell membrane, antioxidant system, and energy metabolism of A. flavus were investigated. The results revealed that fumigation of un-colonized dried red chili powder with 5% formic acid for 24 h inhibited A. flavus growth by 93.29% and toxin synthesis by 99.41%. In contrast, treatment of already colonized chili powder with 10% formic acid inhibited A. flavus colony growth by 50%. Through a three-factor, three-level orthogonal experiment followed by quality testing, the optimal conditions were determined to be 8% formic acid concentration, a UV irradiation distance of 15 cm, and a treatment time of 75 min. This optimized combined treatment reduced the required fumigation time from 24 h to 1.25 h. This technique achieved complete suppression of aflatoxin B1 synthesis on un-colonized dried red chili powder. On already colonized chili powder, the mycelial growth inhibition rate was 48.05 ± 6.68%, and aflatoxin B1 synthesis was inhibited by 91.32 ± 3.15%. Quality assessment revealed that the UV-formic acid co-treatment parameters did not significantly affect key quality indicators including color, capsaicin content, total phenolic content (p > 0.05). Furthermore, UV-formic acid treatment disrupt the cell membrane structure of A. flavus, impairs its antioxidant and energy metabolism systems, and induces mitochondrial dysfunction. The study confirmed the synergistic antifungal effect of formic acid and UV, providing a potential industrialized solution for enhancing the safety and storage stability of dried chili products.